Z prawnej problematyki aktualizacji ewidencji gruntów i budynków - Leśkiewicz, Katarzyna (Wydawnictwo Naukowe UAM, 2016)
The aim of the paper was to establish the circumstances under which an agricultural land loses its agricultural character and may consequently be redefined and classified in the register of land and buildings as a different type of usable land and entered under a heading ‘urbanised undeveloped land or land in the process of being developed’. As explained in the conclusions, only an actual commencement of a construction as referred to in the Act – Building Law, properly documented and reported to local authorities, can effectively create grounds for an exclusion of agricultural land from agricultural production in the understanding of the provisions on the protection of agricultural and forestry land, on which basis the reclassification of the land in the land and buildings register may be made.

L’obiettivo delle considerazioni svolte è di stabilire in quali circostanze il fondo agricolo perde “il carattere rurale” in modo da rendere possibile la riqualificazione ad un altro tipo di uso del suolo nell’inventario corrente del catasto fondiario e edilizio, nonché l’assegnazione soprattutto a “terreni urbanizzati non edificati o terreni urbanizzabili”. Nella parte conclusiva l’autrice afferma tra l’altro che solo l’inizio dei lavori ai sensi delle norme edilizie, il quale porta veramente a escludere i fondi dalla produzione agricola ai sensi delle norme sulla protezione dei fondi agricoli e forestali, con adeguata documentazione e comunicazione al presidente dell’autorità distrettuale competente, può costituire la base per la riqualificazione nel catasto fondiario e edilizio nell’ambito sopra indicato.
Legal aspects of updating registers of land and buildings
Della problematica giuridica dell’attualizzazione del catasto fondiario ed edilizio